The effect of creatine monohydrate supplement on stroke volume during high intensity aerobic exercise in non active adults - A. R. Amani (H.S. Skovoroda Kharkov National Pedagogical University, 2018)
Purpose: Creatine is the most popular supplement to improve body composition and anaerobic performance. There are some other properties of creatine with regard to fitness and aerobic performance. The purpose of current study is to determination of creatine supplement intervention on stroke volume. Material: 38 inactive adult postgraduate students had been divided (n=20) into two groups where the treatment in weight was 76.34 ± 11.73 and height was 174.89 ± 5.82 while placebo group in weight was 81.83 ± 13.10 and height was 176.29 ± 5.2. Results: The result of this research shows that there is no significant effect on the stroke volume during high intensity aerobic exercise. The results of the data in present study also show that there is no effective intervention by the creatine monohydrate supplement on the stroke volume during exercise. However it is showed that there is an increase of stroke volume from the pre to post test in treatment group while the placebo group does not have any increase and the group's stroke volume has decreased from the pre test to the post test. Conclusion: Stroke volume normally reduce during final step high intensity exercise. By the way the current research figured that decreasing of stoke volume at final steps of incremental exercise will be with slow latency at resulted by creatine monohydrate supplements.